Análogos experimentais de evolução cultural: o efeito das conseqüências culturais - Bullerjhann, Paula Barcellos (2009)
To many behavior analysts, the concern about social phenomena has been subject of research and discussion. Some of these researchers have been devoted to intervention in the contents generated by these phenomena, while the other part dedicates to formulation of principles which describes the behavioral processes in a cultural level. This work fits in the second group of research, especially concerning the process involving the selection of the product of interlocking behavioral contingencies, by a cultural consequence. Two experiments were carried out. In experiment 1, a contingency between the performance of each participant and a consequence with supposed reinforcing value was manipulated as was another contingency between a product generated by the group performance of two, three and even four participants and a supposedly reinforcing consequence. Four experimental conditions were performed: (1) selection of the operant behavior; (2) consequences upon the aggregate product; (3) increasing the number of participants in relation to phase 2; and (4) change of generations. In experiment 2, there were two participants in each generation. There wasn't any manipulation of the contingency involving the aggregate product of the interrelation of the behavior of the participants, and three experimental conditions were planned. The results indicate that in experiment 1 there was co-ordination in the behavior of the participants and a systematic outcome of aggregate product, even when the selected product generated the loss of the individual consequence. This generation was sustained even throughout the successive switching of participants. In experiment 2, the interrelations of the participants and the maintenance of the pattern reinforced in the operant phase remained after a few generations. These results show that the manipulations in both experiments were effective in producing experimental analogous of social phenomena and, also, the consequence with supposed selective value was a relevant differential in the cultural practices of both groups